Clinical significance of co-expression of MYC and BCL2 protein in aggressive B-cell lymphomas treated with a second line immunochemotherapy. Issue 6 (2nd June 2016) - Miura, Katsuhiro; Takahashi, Hiromichi; Nakagawa, Masaru; Izu, Asami; Sugitani, Masahiko; Kurita, Daisuke; Sakagami, Masashi; Ohtake, Shimon; Uchino, Yoshihito; Hojo, Atsuko; Kodaira, Hitomi; Yagi, Mai; et al.
Abstract: The clinical significance of concurrent expression of MYC and BCL2 protein, known as "double-expressor lymphoma" (DEL), among patients with relapsed or refractory aggressive B-cell lymphomas, remains unclear. A retrospective analysis was performed of 38 patients treated with a salvage treatment consisting of rituximab, ifosfamide, etoposide, cytarabine and dexamethasone followed by consolidative high-dose chemotherapies. A total of 17 cases (45%) were categorized as DEL using immunohistochemical assay with a cut-off value of positivity of 40% for MYC and 50% for BCL2, respectively. DEL was associated with a lower overall response rate (35% vs 71%, p = 0.0481), worse 2-year progression-free survival (9% vs 67%, p = 0.001) and overall survival (35% vs 71%, p = 0.037). This analysis suggests that DEL is common among patients with relapsed/refractory aggressive B-cell lymphomas and that such patients require novel treatment strategies.